CNS hemangioblastomatosis in a patient without von Hippel–Lindau disease. (April 2017) - Franco, Arie; Pytel, Peter; Lukas, Rimas V; Chennamaneni, Rupa; Collins, John M
We report on a case of disseminated CNS hemangioblastoma, also referred to as hemangioblastomatosis, involving the supratentorial compartment and the entire spine. The patient presented with new onset headache, gait difficulties and memory deficits many years following resection of a hemangioblastoma from the cerebellum. The patient's family history was negative for von Hippel–Lindau (VHL) disease, and his personal history was negative for any additional VHL-defining lesions. Imaging revealed extensive dural caking and nodularity both supratentorially and in the spine, along with scattered parenchymal tumors showing a more typical appearance for hemangioblastoma. Biopsy of the dural thickening revealed histologic features compatible with hemangioblastoma. Genetic testing for VHL was eventually completed, and no evidence of a germline VHL mutation was detected.